2001
DOI: 10.1016/s0002-9440(10)63944-2
|View full text |Cite
|
Sign up to set email alerts
|

NHE-RF, a Merlin-Interacting Protein, Is Primarily Expressed in Luminal Epithelia, Proliferative Endometrium, and Estrogen Receptor-Positive Breast Carcinomas

Abstract: NHE-RF, a regulatory cofactor for NHE (Na(+)-H(+) exchanger) type 3, interacts with ion transporters and receptors through its PDZ domains and with the MERM proteins (merlin, ezrin, radixin and moesin) via its carboxyl terminus. Thus, NHE-RF may act as a multifunctional adaptor protein and play a role in the assembly of signal transduction complexes, linking ion channels and receptors to the actin cytoskeleton. NHE-RF expression is up-regulated in response to estrogen in estrogen receptor-positive breast carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
100
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(115 citation statements)
references
References 19 publications
13
100
1
1
Order By: Relevance
“…EBP50 is present at the plasma membrane in physiological conditions, but often displays ectopic cytoplasmic expression in cholangiocarcinoma tumors. Similar cytoplasmic expression of EBP50 has been described in other human carcinomas, including breast, liver (hepatocellular carcinoma), brain and colon (Stemmer-Rachamimov et al, 2001;Shibata et al, 2003;Cardone et al, 2007;Song et al, 2007;Hayashi et al, 2010;Molina et al, 2010). In these tumors, we show an association between EBP50 cytoplasmic expression and the presence of EGFR at …”
Section: Loss Of Ebp50-egfr Interplay In Biliary Carcinomasupporting
confidence: 87%
“…EBP50 is present at the plasma membrane in physiological conditions, but often displays ectopic cytoplasmic expression in cholangiocarcinoma tumors. Similar cytoplasmic expression of EBP50 has been described in other human carcinomas, including breast, liver (hepatocellular carcinoma), brain and colon (Stemmer-Rachamimov et al, 2001;Shibata et al, 2003;Cardone et al, 2007;Song et al, 2007;Hayashi et al, 2010;Molina et al, 2010). In these tumors, we show an association between EBP50 cytoplasmic expression and the presence of EGFR at …”
Section: Loss Of Ebp50-egfr Interplay In Biliary Carcinomasupporting
confidence: 87%
“…EBP50 is reported to increase in human breast cancer and may have an oncogenic function. 19 We found over-expression of EBP50 and a close association between EBP50 and ␤-catenin accumulation in human HCC. Our study also revealed that EBP50 potentiates ␤-catenin/TCF-mediated transcription.…”
mentioning
confidence: 63%
“…It was also previously reported that EBP50 is overexpressed and redistributed to the cytoplasm and/or nucleus of proliferative cells in hepatocellular carcinoma 8 and in estrogen stimulated-tissues, ie, in endometrium and breast tumors. 7,9,10 Although EBP50 was first postulated as a mitogenic factor, 6 it was subsequently shown to act either as an oncogene 8,9,11,13 or as a tumor suppressor, 14 -16,33,34 and so far its actual impact on cell proliferation has been unclear. Here, on the basis of gene silencing, we could clearly show that EBP50 controls proliferation positively in biliary epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The EBP50 gene possesses 13 half-estrogen responsive elements and is overexpressed in response to estrogens in proliferative mammary and endometrial cells. 4,7,9,10,43 Notably, 17␤-estradiol was recently shown to increase the amount of EBP50 in the nuclear fraction of human airway epithelial cells. 44 In addition, cholangiocyte proliferation is regulated by cyclic AMP, 45 which has also been shown to induce an intracellular redistribution of EBP50 in renal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation